Community Acceptance of The Covid-19 Vaccination Based on Health Behavior Theory (Health Belief Model and Theory of Planned Behavior) - Fitrijaningsih Fitrijaningsih (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
The availability and introduction of the COVID-19 vaccine as a new vaccine against SARS-CoV-2 are accompanied by challenges related to public acceptance from various circles. Vaccination is part of the main protective behavior against the COVID-19 pandemic. Identification of factors related to vaccine acceptance is needed to establish policies and formulate appropriate education for the community. This literature study was conducted by collecting data in the form of open access journals obtained from Google Scholar. The selection results determined that seven selected journals from abroad had compatibility between the topics and constructs in the Health Belief Model/HBM and Theory of Planned Behavior/TPB. More than 72% of respondents indicated their willingness to vaccinate against COVID-19. From the HBM point of view, individual perceptions of severity and susceptibility to COVID-19 have a positive correlation to vaccine acceptance along with perceived benefits. On the other hand, the negative correlation with vaccine acceptance arises due to public doubts regarding its side effects, efficacy, safety, and halalness. Subjective norm originating from policymakers has the most influential role on vaccine acceptance as a construct of PBT. HBM and TPB can be used as a tool to find out the motivations and obstacles that affect people's attitudes towards the COVID-19 vaccine. The right strategy in increasing awareness and acceptance of the COVID-19 vaccine needs to be done to maintain trust and reduce public doubts about the COVID-19 vaccine so that vaccination coverage can be achieved maximally to achieve herd immunity.